2011
DOI: 10.1093/jpepsy/jsq116
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Emotional and Behavior Problems in Pediatric Primary Care Serving Rural Children

Abstract: These data replicate previous findings showing high rates of parent-rated psychosocial problems in pediatric primary care. Given the prevalence of these problems in primary care and parents' frequent help seeking in this setting, more research is needed on innovative approaches to integrated care in rural settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 37 publications
5
48
1
Order By: Relevance
“…These data are proportionate with Polaha et al, [26] who showed such problems are predominant in rural Children. Meanwhile, our findings were not in the agreement with the results of Elbedour et al, [27] who reported that Bedouin children had higher levels of fear, inattention, and hyperactivity behaviour than urban children.…”
Section: Discussionsupporting
confidence: 82%
“…These data are proportionate with Polaha et al, [26] who showed such problems are predominant in rural Children. Meanwhile, our findings were not in the agreement with the results of Elbedour et al, [27] who reported that Bedouin children had higher levels of fear, inattention, and hyperactivity behaviour than urban children.…”
Section: Discussionsupporting
confidence: 82%
“…However, of the children in the pediatric patients group, 34.1 and 18.0 %, respectively, had abnormal and borderline total difficulties scores, suggesting possible psychiatrics disturbances. There is a higher prevalence of emotional and behavior problems in pediatric primary care compared with the prevalence measured in community samples (Bilfield et al 2006; Polaha et al 2011). Our findings are in agreement with other studies that showed higher SDQ scores in clinical nonpsychiatric samples.…”
Section: Discussionmentioning
confidence: 87%
“…Consequently, because there are limited resources to address severe eating concerns in group-based programs, this can result in the participation of children who may not be appropriate for lifestyle weight management programs. Children in rural areas may also be more likely to have other significant health and mental health challenges (Cayce et al, 2005;Polaha, Dalton, & Allen, 2011), such as developmental delays and behavioral disorders, which may not be adequately identified or treated due to decreased access to care. These comorbidities may impact child participation in a group setting and may present obstacles to helping families adopt healthier lifestyle behaviors, ultimately limiting benefits from being in a group-based weight management program.…”
Section: Access To Servicesmentioning
confidence: 99%